QUALITY BASED PRODUCTIVITY OF FERTILIZER, TECHNOLOGY AND CAPITAL - Rosliana Rosliana; Oktarini Khamilah Siregar; Rusiadi Rusiadi; Ade Novalina; Bhaktiar Efendi; Lia Nazliaan Nasution; Suhendi Suhendi; Diwayana Putri Nasution (Universitas Kristen Indonesia Toraja, 2022)
The research objective was to determine the effect of the quality of fertilizer, technology and capital on the productivity of the people in Tunas Harapan Village, Gunung Meriah District, Aceh Singkil Regency. The population in this study was the community in Tunas Harapan Village, Gunung Meriah District, Aceh Singkil Regency, totaling 198 people, then the determination technique was purposive random sampling. The data collection technique used a questionnaire with a Likert measurement scale. The results of multiple regression analysis are Y = 7.772 + 0.257X1 + 0.1932 + 0.348X3 + e which shows the quality of fertilizer, technology and capital have a positive and significant effect on the productivity of the people. While the results of the test (t) or partial test show that the quality of fertilizer has a positive and significant effect on community productivity where it can be seen that the value of t count = 2.359 > t table 2.034, the technology variable has a positive and significant effect on community productivity where it can be seen that the value of t count = 2.137 > t table 2.034, and capital also has a positive and significant effect on the productivity of the people where it can be seen that the value of t count = 2.533 > t table 2.034. Then the coefficient of determination (R2) is 0.823 (82.3%). So that it can be said that 82.3% of the variation in the dependent variable, namely the quality of fertilizer, technology and capital in the model has contributed to the productivity of the community in Tunas Harapan Village, Gunung Meriah District, Aceh Singkil Regency, while the remaining 17.7% is influenced by other variables outside the model